Comparison of STONE score, Guy's stone score and Clinical Research Office of the Endourological Society (CROES) score as predictive tools for percutaneous nephrolithotomy outcome: a prospective study. (4th August 2020) - Biswas, Krishnendu; Gupta, Shailendra Kumar; Tak, Gopal R.; Ganpule, Arvind P.; Sabnis, Ravindra B.; Desai, Mahesh R.
Abstract : Objective: To evaluate which among the three scoring systems used to predict stone‐free status (SFS) after percutaneous nephrolithotomy (PCNL), namely Guy's stone score (GSS), STONE nephrolithometry score and Clinical Research Office of the Endourological Society (CROES) nephrolithometry nomogram, is the most accurate predictor of SFS. Method and Materials: We prospectively included all patients who underwent PCNL (tract size >24 F) at our hospital between July 2017 and January 2019. All demographic and peri‐operative data were tabulated including calculation of GSS, STONE score and CROES nomogram score using preoperative computed tomography. Comparison of the 'stone‐free' group and 'residual‐stone' group was carried out using standard statistical methods. Results: A total of 252 patients were enrolled. The mean GSS, STONE score and CROES score in the stone‐free group was 1.60, 6.98 and 212.27, respectively, and in the residual stone group group it was 2.93, 8.98 and 129.89, respectively ( P < 0.001 in each). Receiver‐operating characteristic (ROC) curves showed that all three scoring systems had similar predictive accuracy for post‐PCNL SFS, with STONE score having the highest area under the ROC curve value (0.852). GSS was significantly associated with operating time, estimated blood loss (EBL) and length of hospital stay (LOS; P < 0.001 in each). STONE score and CROES score were both significantly associated with EBL ( P = 0.029 and 0.001, respectively). Conclusion: All three scoring systems are equally predictive of post‐PCNL SFS. EBL is significantly associated with all three scoring systems, while GSS is also associated with operating time and LOS.